Assessing cardiovascular disease: looking beyond cholesterol. Issue 5 (18th October 2022) - Kendrick, Malcolm
Abstract : Purpose of review: The low-density lipoprotein (LDL)-cholesterol level is a weak predictor of developing cardiovascular (CV) disease and can only explain a small proportion of CV risk. It is not used to determine CV risk on either the atherosclerotic cardiovascular disease (ASCVD) calculator in the United States, or the Qrisk3 in the UK. A study in JAMA in 2022 suggested that ' the absolute benefits of statins are modest and may not be strongly mediated through the degree of LDL reduction '. Perhaps it is time to look beyond cholesterol to a different causal model – the 'thrombogenic' model of ASCVD. Recent findings: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) pandemic demonstrated that infectious agents damage the endothelium and the glycocalyx – the glycoprotein layer protecting underlying endothelial cells. There are numerous other conditions leading to this kind of damage, which can trigger thrombus formation, causing strokes and myocardial infarctions. Although these are acute events, they highlight a mechanism for the development of ASCVD which centres on endothelial damage and thrombus formation as both the primary causal mechanism for acute events, and the driver behind progression towards atherosclerotic plaque development. Summary: The cholesterol hypothesis, that a raised LDL is directly causal for ASCVD, does not adequately explain cardiovascular risk in individuals, or populations. An alternative 'thrombogenic' hypothesis is proposed as a more valid causal model.